Citizen Paddle Project: prividing an experience with racket sport to students from physical education course and elementary public school - dos Santos Sanchez, Mariza de Fátima (2020)
BACKGROUND: Paddle is sport, which use a racket to play. This physical entertainment spread in South America, mainly in Argentina and Uruguay, in the last decade of 1980. Even though it is a contemporaneous sport in their culture, it does not be included in the academic curriculum of the physical education course.OBJECTIVE: Contextualizing this situation and overcoming the lack in the academy program of paddle education, this work had the aim to notify the impact of Citizen Paddle Project experience during physical education classes on Federal University of Pampa. This project provided not only the knowledge and familiarity with paddle in the academic environment, but also the opportunity of students from the elementary public education of Uruguaiana city to practice this sport.METHODS: The courts were provided by the Engenho Paddle Sport Center twice a week during July to December of 2019. The project consisted in the weekly meeting with students of the Physical Education course at the University; and separately, with students of elementary public school. The project involved students from Physical Education course (10), and 5th grade of elementary school (19); administrative technicians (2); and professors (2). RESULTS: It was possible to observe the interest and motivation of students during the paddle project. Through this experience, the academic students could reflect on the new systematization and methodologies that could facilitate the application of paddle education in their professional area. In addition, the elementary school students had the opportunity to experience this modality, which is still unexplored in their physical education classes.CONCLUSION: Citizen Paddle Project impacted greatly both academic and elementary students. It created an environment with new possibilities in the professional qualification of physical educator. Moreover, it was improved the intellectual and motor skills of students by the development of paddle abilities.